2019
DOI: 10.1016/j.isci.2019.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane Protein Aptamer Induces Cooperative Signaling by the EPO Receptor and the Cytokine Receptor β-Common Subunit

Abstract: Summary The erythropoietin receptor (EPOR) plays an essential role in erythropoiesis and other cellular processes by forming distinct signaling complexes composed of EPOR homodimers or hetero-oligomers between the EPOR and another receptor, but the mechanism of heteroreceptor assembly and signaling is poorly understood. We report here a 46-residue, artificial transmembrane protein aptamer, designated ELI-3, that binds and activates the EPOR and induces growth factor independence in murine BaF3 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…Signaling through these receptors and/or receptor complexes demonstrate distinct biological outcomes, while the molecular mechanism of such signaling is mainly unknown. For example, the study of He et al [ 56 ] revealed that in contrast with the active EPOR homodimer, the EPOR/βcR complex does not utilize the cytoplasmic tyrosines for EPOR signaling.…”
Section: Epor/pi3k/akt and Epor/mapk In Non-hematopoietic Tissuesmentioning
confidence: 99%
“…Signaling through these receptors and/or receptor complexes demonstrate distinct biological outcomes, while the molecular mechanism of such signaling is mainly unknown. For example, the study of He et al [ 56 ] revealed that in contrast with the active EPOR homodimer, the EPOR/βcR complex does not utilize the cytoplasmic tyrosines for EPOR signaling.…”
Section: Epor/pi3k/akt and Epor/mapk In Non-hematopoietic Tissuesmentioning
confidence: 99%
“…Traptamers that target other receptors have been isolated. For example, DiMaio and co-workers (196,199) set up a screen for transmembrane sequences that induce IL-3-independent proliferation of BaF3 cells engineered to express EpoR, but not parental BaF3 cells lacking EpoR expression. This led to the discovery of traptamers that activate EpoR but not PDGF␤R.…”
Section: Jbc Reviews: Using Short Peptides To Study Large Receptorsmentioning
confidence: 99%
“…Transmembrane Proteins (TMPs), as an essential type of Membrane Proteins(MPs), span the entire biological membrane with segments exposed to both inside and outside of the lipid bilayers (Stillwell 2016). Since TMPs play numerous roles in basic physiology and pathophysiology (Puder, Fischer, and Mierke 2019;He et al 2019;Oguro and Imaoka 2019), they are major targets for nearly half of the known drugs on the current therapeutics market. In the field of drug development, for one thing, interaction information of TMPs helps researchers understand the drug interactions on a molecular biology level, leading the drug design more accurate and efficient (Lee et al 2007).…”
Section: Introductionmentioning
confidence: 99%